Genesis and development of interference of supranational into the national criminal procedural law - Samaryn, Vadzim I. (Journal of the Belarusian State University. Law, 2020)
The article presents a vision of the international legal paradigm of the modern criminal procedure. According to the author, this paradigm has developed as a result of the internationalization of the criminal procedure and is a mediation in the criminal procedure legislation of the principles enshrined in international legal acts and the admission of the direct application of international treaties in the criminal procedure. The difficulty of allocating a time frame for the stages of development of the penetration of supranational into the national criminal procedure is noted since each state has passed and is passing its path of transformation of the criminal procedure. The author identifies five stages of such interference: 1) ensuring the unhindered activity of diplomatic agents; 2) consolidation of the legal institution of international legal assistance in criminal matters at the national level; 3) the implementation of universally recognized norms of human rights in the field of criminal procedure; 4) recognition of international judicial protection at the national level; 5) direct harmonization of criminal procedure law within the framework of a supranational organization.